Dominica : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2006)
Dominica showed a commendable progress under the Poverty Reduction and Growth Facility (PRGF) program. Executive Directors welcomed the strong macroeconomic performance, fiscal adjustment, and collaborative debt restructuring effort. They appreciated the introduction of a value-added tax (VAT) and an excise tax and stressed the need for the implementation of robust structural reforms to promote a sustained strong growth and poverty reduction. They agreed that the strong implementation of the policies under the program will help balance the risks and provide adequate performance.